PENGGUNAAN TEKNIK PERMAINAN PAIRE MINIMALE UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA PERANCIS - Prianti, Andini Nur (2016)
This study aims to know: (l) the results of student learning before and after using the minimal pairs game tchnique; (2) effectiveness of minimal pairs game technique; and (3) students' thought on minimal pairs game. This study uses a quantitative method with pre-experimental research design: One Group Pre-test and Post-test. The population of this study is characteristic of French speaking skills at the level of the pronunciation of the third semester students of the academic year 2016/2017 with a sample of 30 students. Data obtained through tests and questionnaires. The results showed that the average value of pre-test and post-test increased by 4.33%. In addition, based on the result of t test, minimal pairs game technique is effectively improving the speaking skills of students at the level of pronunciation, i.e. tcount is greater than the value of ttable (5.69> 2.05). Based on questionnaire data analysis, the researcher concluded that the technique of minimal pairs game contributes positively to the ability of a student to pronounce. The advantages of minimal pairs game technique among others, are: (1) interesting; (2) an alternative to train pronunciation; (3) help students to train the pronunciation of the word with an identical sound; (4) increase the motivation to learn; (5) learning is more fun. On the other hand, the disadvantages are as follows: (1) it may require a longer learning period; (2) the rule is quite difficult; (3) the cards are difficult to obtain; (4) a lot of minimal pairs should be prepared; (5) it must be played together. Based on these results, this study is expected to be one of the reference materials for teaching French language subjects.;---Penelitian ini bertujuan untuk mengetahui : (l) hasil belajar mahasiswa sebelum dan sesudah menggunakan teknik permainan paire minimale; (2) efektivitas teknik permainan paire minimale; dan (3) penilaian mahasiswa terhadap teknik permainan paire minimale. Penelitian ini menggunakan metode kuantitatif dengan desain penelitian pra-eksperimental : One Group Pretest-Posttest. Populasi penelitian ini adalah keterampilan berbicara bahasa Perancis pada tataran pelafalan mahasiswa semester III tahun ajaran 2016/2017 dengan sampel penelitian 30 orang mahasiswa. Data diperoleh melalui tes dan angket. Hasil penelitian menunjukkan bahwa nilai rata-rata prates dan pascates meningkat 4,33%. Selain itu, berdasarkan hasil uji t teknik permainan paire minimale efektif untuk meningkatkan keterampilan berbicara mahasiswa pada tataran pelafalan, yaitu nilai thitung lebih besar dari nilai ttabel (5,69 > 2,05). Berdasarkan analisis data angket, peneliti menyimpulkan bahwa teknik permainan paire minimale berkontribusi positif terhadap kemampuan melafalkan mahasiswa. Kelebihan teknik permainan paire minimale, antara lain : (1) menarik; (2) dapat menjadi alternatif untuk melatih pelafalan; (3) membantu melatih pelafalan pada kata dengan bunyi hampir serupa; (4) meningkatkan motivasi belajar; (5) pembelajaran lebih menyenangkan. Adapun kekurangannya yaitu : (1) perlu waktu pembelajaran yang lama; (2) aturan main cukup sulit; (3) kartu sulit didapatkan; (4) kata pasangan minimal harus dalam jumlah yang cukup banyak; (5) harus dimainkan bersama-sama. Berdasarkan hasil penelitian tersebut, peneliti merekomendasikan teknik permainan ini sebagai teknik pembelajaran alternatif.